1998
DOI: 10.1074/jbc.273.41.26421
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Protein Targeting to Glycogen (PTG) in Rat Hepatocytes Causes Profound Activation of Glycogen Synthesis Independent of Normal Hormone- and Substrate-mediated Regulatory Mechanisms

Abstract: Protein targeting to glycogen (PTG), also known as PPP1R5, is a widely expressed member of a growing family of proteins that target protein phosphatase-1 (PP-1) to glycogen particles. Because PTG also binds to glycogen synthase and phosphorylase kinase, it has been suggested that it serves as a "scaffold" for efficient activation of glycogen synthesis. However, very little is known about the metabolic effects of PTG. In this study, we have used recombinant adenovirus to overexpress PTG in primary rat hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 30 publications
12
69
0
Order By: Relevance
“…G L (R4) is expressed predominantly in liver and to a lesser extent in heart and human skeletal muscle (6,7), PTG is expressed in several tissues including liver and skeletal muscle (8 -10), and R6 is expressed ubiquitously (11). Both G L and PTG show adaptive changes in expression in rat liver in response to changes in insulin status (5), and the physiological role of these changes has been confirmed from studies (12,13) in hepatocytes, which showed glycogen synthase activation and increased glycogen storage when G L and PTG were overexpressed.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…G L (R4) is expressed predominantly in liver and to a lesser extent in heart and human skeletal muscle (6,7), PTG is expressed in several tissues including liver and skeletal muscle (8 -10), and R6 is expressed ubiquitously (11). Both G L and PTG show adaptive changes in expression in rat liver in response to changes in insulin status (5), and the physiological role of these changes has been confirmed from studies (12,13) in hepatocytes, which showed glycogen synthase activation and increased glycogen storage when G L and PTG were overexpressed.…”
mentioning
confidence: 73%
“…The effects of glucose and PTG were not additive suggesting that PTG mimics the effect of glucose. DISCUSSION PTG expression activates glycogen synthase and stimulates glycogen storage in various cell types (8,12,13,21). Because phosphorylase a has major roles in the control of synthase phosphatase (1) and the rate of glycogen synthesis in hepatocytes (15, 29), we tested the role of inactivation of phosphorylase in the glycogenic action of PTG in hepatocytes.…”
Section: Ptg Expression Counteracts the Acute And Sustained Activatiomentioning
confidence: 99%
See 1 more Smart Citation
“…3c), reaching values that were nearly three times higher than those in freshly isolated islets from fed mice. Thus, in contrast to other models of PTG overexpression [31], glycogen accumulation in beta cells of PTG OE mice is subject to regulation and can be modulated both in vivo in response to fasting and in vitro by incubation at a range of glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that in beta cells of PTG OE mice, in contrast to other mouse models of PTG overexpression [31], glycogen stores can be mobilised when extracellular glucose is low. In line with prior work [4], glycogenolysis in beta cells of PTG OE mice after an overnight fast may stimulate insulin release and explain increased insulin levels when these animals are subjected to fasting.…”
Section: Discussionmentioning
confidence: 99%